Design, synthesis and biological evaluation of novel quinoline‐based carboxylic hydrazides as anti‐tubercular agents. (24th June 2016) - Chander, Subhash; Ashok, Penta; Cappoen, Davie; Cos, Paul; Murugesan, Sankaranarayanan
Abstract : In this study, seventeen novel quinoline‐based carboxylic hydrazides were designed as potential anti‐tubercular agents using molecular hybridization approach and evaluated in‐silico for drug‐likeness behavior. The compounds were synthesized, purified, and characterized using spectral techniques (like FTIR, 1 H NMR, and Mass). The in‐vitro anti‐tubercular activity (against Mycobacterium tuberculosis H37Ra) and cytotoxicity against human lung fibroblast cells were studied. Among the tested hydrazides, four compounds (6h, 6j, 6l, and6m ) exhibited significant anti‐tubercular activity with MIC values below 20  μ g/mL. The two most potent compounds of the series, 6j and6m exhibited MIC values 7.70 and 7.13  μ g/mL, respectively, against M. tuberculosis with selectivity index >26. Structure–activity relationship studies were performed for the tested compounds in order to explore the effect of substitution pattern on the anti‐tubercular activity of the synthesized compounds. Abstract : Seventeen, novel quinoline‐based carboxylic hydrazides (6a–q ) were designed, synthesized, and evaluated for anti‐Mtb and cytotoxicity properties, in which compounds6h, 6j, 6l, and6m exhibited significant anti‐Mtb activity (MIC < 20  μ g/mL). None of the compound exhibited cytotoxicity against lung fibroblast cells at tested concentration (512  μ m ). Structure–activity relationship study of the tested compounds revealed that electron withdrawing group of moderate to large size especially at para position of phenyl ring significantly increased the potency against anti‐Mtb while retaining a good safety index.